Legal Implications of Substantive Typing Errors in The Preparation of Notarial Deeds (RI Supreme Court Decision Number 1069 K/PDT/2020) - Sulistyawali Prabesa, Putu Shannen (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
The making of notarial deeds is an integral part of the civil law system in Indonesia which has perfect evidentiary power (authentic deeds). However, in practice, errors often occur in the process of making deeds, both formally and substantively, which can give rise to legal disputes in the future. This study aims to analyze the legal implications of substantive errors in the making of notarial deeds based on the Decision of the Supreme Court of the Republic of Indonesia Number 1069 K/Pdt/2020. This study uses a normative legal method with a statutory approach and a legal concept analysis approach. The data sources used are secondary data through literature studies including primary legal materials, secondary legal materials, and tertiary legal materials. Here, the data collection method uses the literature study method and is analyzed using the content analysis method. The results of the study indicate that substantive errors made by notaries, such as including identities or statements that do not comply with the wishes of the parties, can result in the cancellation of the deed as authentic evidence. In its ruling, the Supreme Court emphasized that substantive errors constitute a violation of the principles of prudence and notarial responsibility, which can result in legal consequences in the form of civil liability, even administrative or criminal sanctions. Therefore, notaries are required to carry out their official functions professionally, diligently, and in accordance with applicable laws.